2021
DOI: 10.3389/fpls.2021.782465
|View full text |Cite
|
Sign up to set email alerts
|

Acclimating Cucumber Plants to Blue Supplemental Light Promotes Growth in Full Sunlight

Abstract: Raising young plants is important for modern greenhouse production. Upon transfer from the raising to the production environment, young plants should maximize light use efficiency while minimizing deleterious effects associated with exposure to high light (HL) intensity. The light spectrum may be used to establish desired traits, but how plants acclimated to a given spectrum respond to HL intensity exposure is less well explored. Cucumber (Cucumis sativus) seedlings were grown in a greenhouse in low-intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Although LED lighting offers complete spectral freedom, this comes at the expense of spectral consistency between growers and setups, which can make it difficult to unravel the effects of differing spectral conditions on crop performance. Despite this, there is an overall trend for greater biomass with increasing fractions of red light, whereas higher fractions of blue tend to increase photosynthetic capacity, which is beneficial under higher light intensities (e.g., under sunlight) (Hogewoning et al 2010;Kaiser et al 2019a;Kang et al 2021), pigment content, and secondary metabolite synthesis (Tables 1 and 2). Although these general trends are worth adhering to (and a basic protocol for determining the optimal R:B ratio is provided in Fig.…”
Section: Led Light Growth Spectra: the Par Regionmentioning
confidence: 99%
“…Although LED lighting offers complete spectral freedom, this comes at the expense of spectral consistency between growers and setups, which can make it difficult to unravel the effects of differing spectral conditions on crop performance. Despite this, there is an overall trend for greater biomass with increasing fractions of red light, whereas higher fractions of blue tend to increase photosynthetic capacity, which is beneficial under higher light intensities (e.g., under sunlight) (Hogewoning et al 2010;Kaiser et al 2019a;Kang et al 2021), pigment content, and secondary metabolite synthesis (Tables 1 and 2). Although these general trends are worth adhering to (and a basic protocol for determining the optimal R:B ratio is provided in Fig.…”
Section: Led Light Growth Spectra: the Par Regionmentioning
confidence: 99%
“…It is assumed that mixed RL and BL with higher ratio of BL were more inhibitive of hypocotyl and leaf elongation and inducing in the sweet pepper seedlings a more compact morphology with shorter stems and smaller leaf areas than monochromatic BL. These results indicated that increasing BL could inhibit cell division and expansion ( Kang et al., 2021 ). Furthermore, lower levels of GA and IAA under a low RL/BL ratio of 1R3B may lead to reduced elongation of pepper seedlings’ shoots ( Islam et al., 2014 ; Matsuo et al., 2019 ).…”
Section: Discussionmentioning
confidence: 93%
“…Hence, RL significantly reduced P n and F v / F m , which might result in acceleration of leaf senescence ( Su et al., 2014 ). The photodamaged PSII induced by RL could be alleviated by BL, which could benefit pepper seedling growth by improving light use efficiency and diminish photoinhibition ( Miao et al., 2019 ; Kang et al., 2021 ). On the other hand, the P n and F v / F m , Φ PSII , ETR and qP of seedlings exposed to 3R1B treatment was found to be significantly higher than those of other light spectra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cucumbers, supplemental blue LEDs at 15 µmol m −2 s −1 with high-pressure sodium (HPS) lamps (90 µmol m −2 s −1 ) for 18 h d −1 not only decreased hypocotyls’ elongation, but also increased the leaf area, increased the fresh and dry weight, and enhanced their development, compared with HPS only [ 140 ]. In the same species grown in a greenhouse under low-intensity sunlight (about 2.7 mol m −2 d −1 ), 10 days of SL with blue LEDs relative to white, red, or green LEDs (at 120 µmol m −2 s −1 for 10 h d −1 ; 4.3 mol m −2 d −1 ) caused more compact plants with shorter stems and smaller leaf areas, despite similar shoot biomass [ 141 ]. Furthermore, after transferring to full sunlight (10.7 mol m −2 d −1 ), plants from the blue LED treatment developed similar leaf areas and 15% higher shoot biomass, showing better acclimation ability compared to other spectral treatments [ 141 ].…”
Section: Application Of Blue Leds In Mediating Plant Elongation For C...mentioning
confidence: 99%